Pengaruh Suhu dan Lama Penyimpanan terhadap Kadar Nitrit pada Rebusan Bayam Hijau - Hendra Budi Sungkawa; Sugito Sugito (Politeknik Kesehatan Tanjung Karang, 2019)
Spinach is a highly nutritious leaf vegetable that is beneficial to the body, including one of the plants recommended fields to support the Family Nutrition Improvement Business (FNIB). Spinach contains nitrate (NO3-) which is reduced by air will become nitrite (NO2-). Consuming spinach should not be more than 5 hours after cooking, because if consumed in a situation that has been left it can cause poisoning in the body. This study was a quasi-experiment with Griess II examination method with Perkin Elmer's Lambda 25 UV-Vis Spectrophotometer which aims to determine the effect of temperature and storage time on nitrite levels in green spinach stew. The results of data processing showed nitrite levels in green spinach stew stored for 3 hours at 0.017mg/L and 0.038mg/kg, for 6 hours at 0.076mg/L and 0.015mg/kg and for 9 hours at 0.428mg/L and 0.005mg/kg.The level of storage in the room, the lowest value is 0.009mg/L while the highest value is 0.915mg/L. Whereas in the refrigerator storage the lowest value is 0.003mg/L and the highest level is 0.048mg/L. The conclusion in this study is that there are differences in nitrite levels in boiled green spinach which are stored for 3 hours, 6 hours, and 9 hours, and there is an effect of storage temperature on nitrite levels with very strong relationship strength.